Maximizing yogurt firmness as functions of thermal denaturation and milk solids nonfat concentration - Donald, Emily Joy (Kansas State University, 2021)
Gel formation and quality in yogurts may be manipulated by varying yogurt mix heating temperature or altering milk solids nonfat (MSNF) concentration, which impacts the gel structure through the denaturation and aggregation of milk proteins. The overall objective of this research was to produce yogurts with maximum firmness through mix heating treatment and MSNF concentration. During the phase one study, yogurts were produced from mixes with 16% MSNF heated at 70, 78, 86 or 95 ºC for 30 min. As process temperature increased from 70 to 78 ºC, the resultant yogurts exhibited an increasingly firm texture. Yogurt mix heat treatments of 78, 86 and 95 ºC resulted in firmness that did not significantly differ; however, yogurts produced from mixes heated at 95 ºC exhibited decreased quality, ascertained by graininess, which increased. Variations in texture, correlating to protein denaturation and aggregation, were visually observed in microscopic images and microfluidic gel electrophoresis. In the phase two study, variations in yogurts were generated by manipulating milk solids nonfat (MSNF) concentration (9 and 12%) and mix heating temperatures (70, 75, or 85 ºC for 30 min) to produce the firmest yogurt. Yogurt mixes, manufactured from nonfat dry milk, were analyzed using nitrogen fractionation, polyacrylamide gel electrophoresis and fluorescence of Maillard products and soluble tryptophan (FAST) index. Similar to the previous study, combining mix analyses with yogurt’s textural, rheological and quality testing, the relationship between MSNF contents, heating temperature, protein denaturation and gel strength was investigated. The combination of 12% MSNF and 85 ºC produced yogurts with the greatest firmness, storage and loss moduli directly correlating with FAST index. Yogurts produced with 12% MSNF exhibited the lowest syneresis and highest water holding capacities, while mix degree of denaturation increased due to heating temperature, independent of MSNF concentration. Meanwhile, greater MSNF concentration and heating temperature translated to a denser protein gel network, more resistant to compression and shear. Increased MSNF correlates with increased protein content, resulting in additional denaturation and aggregation upon heating, translating to a denser protein gel network. With additional knowledge of the relationship between gel formation, MSNF and heating allows for conditions to be optimized to yield yogurts with maximum firmness. Further research to determine how MSNF concentration affects denaturation and aggregation may potentially lead to the production of firmer yogurts.
Keywords: Yogurt; Whey protein denaturation; Plant-based dairy alternatives